Pembaruan Pilar Hukum Pidana Dalam RUU KUHP - Faisal, Faisal; Rustamaji, Muhammad (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 2 (2021)DO - 10.24843/JMHU.2021.v10.i02.p08, 2021)
The basic idea underlying the reform of  the Criminal Code Bill has an impact on reforming the pillars of criminal law. The purpose of this research is to find out the new direction of criminal law policy regarding criminal acts, criminal responsibility and punishment. The research method uses normative legal research. The results of the research study in the discussion section are the reform of the pillars of criminal law, namely criminal acts, criminal liability, and punishment oriented to the basic idea of ??the value of balance. The reform of the pillars of criminal acts is aimed at broadening the meaning of the legality principle which provides space for living law as a source of law and also creates juridical terminology regarding criminal acts. The pillar of criminal responsibility accommodates the principle of no crime without error. The pillar of punishment is that the purpose of punishment is no longer synonymous with retaliation, but there are efforts to improve the behavior of the perpetrators of crime. The changes in the three pillars are influenced by the basic idea of ??balancing the values ??of Pancasila, namely the values ??of Divinity, Humanity, and Society. Recommendations in strengthening the direction of criminal law reform are needed in formulating criminal provisions outside the Draft Criminal Code that must be in accordance with the basic idea of ??balance which is the ideal of criminal law reform law. Ide dasar yang melandasi pembaruan RUU KUHP berdampak pada pembaruan pilar hukum pidana. Tujuan penelitian untuk mengetahui arah baru kebijakan politik hukum pidana mengenai tindak pidana, pertanggungjawaban pidana dan pemidanaan. Metode penelitian menggunakan penelitian hukum normatif. Hasil kajian penelitian dalam bagian pembahasan ialah pembaruan pilar hukum pidana yakni tindak pidana, pertanggungjawaban pidana, dan pemidanaan berorientasi pada ide dasar nilai keseimbangan. Pembaruan pilar tindak pidana tertuju pada perluasan makna asas legalitas yang memberikan ruang pada hukum yang hidup sebagai sumber hukum dan melahirkan pula terminologi yuridis mengenai tindak pidana. Pilar pertangungjawaban pidana mengakomodasi asas tiada pidana tanpa kesalahan. Pilar pemidanaan bahwa tujuan pemidanaan tidak lagi identik pembalasan akan tetapi ada upaya memperbaiki perilaku dari pelaku kejahatan. Perubahan ketiga pilar tersebut dipengaruhi oleh ide dasar keseimbangan nilai Pancasila yaitu nilai Ketuhanan, Kemanusiaan, dan Kemasyarakatan. Rekomendasi dalam memperkuat arah pembaruan hukum pidana diperlukan dalam merumuskan ketentuan pidana di luar RUU KUHP harus sesuai dengan ide dasar keseimbangan yang menjadi cita hukum pembaruan hukum pidana